La persistencia de una idea: el nacionalismo revolucionario. Del PRI a López Obrador - Hernández Rodríguez, Rogelio (El Colegio de México A.C., 2020)
This essay seeks to show how revolutionary nationalism was for decades the foundation of the institutions and efforts of the post-revolutionary system and of Mexican society. These ideas, which were transformed into government programs and institutions to apply them, produced results that defined the state and its functions, together with the dominant party, as an integral part of this institutional development. The deeper transformation of these principles and of the state itself began with the substitution of economic policy and the resulting change in the elite in power, beginning with the government of President Miguel de la Madrid. However, revolutionary nationalism maintained a presence in the criticism of governments, both pan and pri, after 1988, and constitutes the social underpinning that swept Andrés Manuel López Obrador to power in 2018.